2022
DOI: 10.1007/s12178-022-09811-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Determinants of Health in Spine Surgery

Abstract: Purpose of Review Social determinants of health (SDH) are factors that affect patient health outcomes outside the hospital. SDH are “conditions in the environments where people are born, live, learn, work, play, worship, and age that affect a wide range of health, functioning, and quality-of-life outcomes and risks.” Current literature has shown SDH affecting patient reported outcomes in various specialties; however, there is a dearth in research relating spine surgery with SDH. The aim of this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Patients on Medicaid also had increased post-operative bleeding rates, in addition to increase in-hospital mortality [53] . In an all-encompassing literature review on associations between patient SES and spine surgery outcomes, several additional studies reported that Black patients have longer hospital lengths of stay, higher in-hospital mortality, and higher post-operative readmissions [54] . Additionally, higher educational attainment is associated with less post-operative pain and disability, as well as increased rates of ability to work and return to work by three months and one-year post-operatively [54] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients on Medicaid also had increased post-operative bleeding rates, in addition to increase in-hospital mortality [53] . In an all-encompassing literature review on associations between patient SES and spine surgery outcomes, several additional studies reported that Black patients have longer hospital lengths of stay, higher in-hospital mortality, and higher post-operative readmissions [54] . Additionally, higher educational attainment is associated with less post-operative pain and disability, as well as increased rates of ability to work and return to work by three months and one-year post-operatively [54] .…”
Section: Discussionmentioning
confidence: 99%
“…In an all-encompassing literature review on associations between patient SES and spine surgery outcomes, several additional studies reported that Black patients have longer hospital lengths of stay, higher in-hospital mortality, and higher post-operative readmissions [54] . Additionally, higher educational attainment is associated with less post-operative pain and disability, as well as increased rates of ability to work and return to work by three months and one-year post-operatively [54] . While these studies suggest there are SES disparities regarding post-operative spine surgery outcomes, it has also been demonstrated that patients who live in higher ADI neighborhoods do not have worse long-term physical and mental health after lumbar spine surgery, suggesting that lower SES patients experience similar long-term health benefits as higher SES patients [55] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite growing attention to SDOH and the role of the healthcare sector in addressing them, there are no available scoping reviews of the peer-reviewed literature on hospital and health system-led initiatives to address SDOH. Existing reviews on the topic have focused on specific subtopics of SDOH (e.g., reviews of hospital partnerships to promote population health) ( 23 ), specific SDOH (e.g., health system efforts to address housing) ( 24 ), specific outcomes (e.g., impact of social support on hospital readmission rates) ( 25 ), specific diseases (e.g., impact of social determinants in spine surgery) ( 26 ), or specific populations (e.g., social risks among primary care patients) ( 27 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interventions that target these factors may mitigate inequities in spine surgery outcomes and better inform surgeons in addressing the biases that may influence choice in spine procedures. Determinants like higher education, increased wealth, and quality health insurance coverage have proven to be fundamental to improved health care quality, access, and outcomes 19–22 . For example, Mo et al 23 and Khan et al 24 demonstrated that after accounting for education levels, socioeconomic status, and insurance, African-American patients often suffer worse postoperative spine outcomes compared with Caucasian patients.…”
mentioning
confidence: 99%